2020
DOI: 10.1038/s41467-020-19352-1
|View full text |Cite
|
Sign up to set email alerts
|

ATF4 leads to glaucoma by promoting protein synthesis and ER client protein load

Abstract: The underlying pathological mechanisms of glaucomatous trabecular meshwork (TM) damage and elevation of intraocular pressure (IOP) are poorly understood. Here, we report that the chronic endoplasmic reticulum (ER) stress-induced ATF4-CHOP-GADD34 pathway is activated in TM of human and mouse glaucoma. Expression of ATF4 in TM promotes aberrant protein synthesis and ER client protein load, leading to TM dysfunction and cell death. These events lead to IOP elevation and glaucomatous neurodegeneration. ATF4 intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 86 publications
(125 reference statements)
1
47
0
Order By: Relevance
“…These findings further support our conclusion that reduction of CHOP reduces mutant myocilin via promoting autophagic degradation of mutant myocilin. We have recently shown that chronic ER stress induced ATF4, and CHOP promoted increased protein synthesis, which leads to ER client protein load ( 43 ). It is therefore possible that chronic ER stress–induced protein synthesis and ER client protein load may overwhelm autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings further support our conclusion that reduction of CHOP reduces mutant myocilin via promoting autophagic degradation of mutant myocilin. We have recently shown that chronic ER stress induced ATF4, and CHOP promoted increased protein synthesis, which leads to ER client protein load ( 43 ). It is therefore possible that chronic ER stress–induced protein synthesis and ER client protein load may overwhelm autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…TM3 cells stably expressing DsRed-tagged WT or mutant (Y437H, G364V and Q368X) myocilin were generated by transfecting with plasmid expressing DsRedtagged WT or mutant (Y437H, G364V and Q368X) myocilin containing a G418 selection. The stable cell colonies were then selected using G418 (0.6 mg/ml; Gibco, Life Technologies, Grand Island, NY, USA) containing media and stable cells were maintained in the same medium as described previously (43,68).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zode et al [ 22 ] reported that, the transcriptional factor C/EBP homologous protein (CHOP), a marker for chronic endoplasmic reticulum (ER) stress, is upregulated in the anterior segment tissues, and CHOP deletion reduced ER stress in these tissues and prevented dexamethasone-induced ocular hypertension. Additionally, Kasetti et al have also reported that [ 23 ] activating transcription factor 4 (ATF4)- C/EBP homologous protein (CHOP)– growth arrest and DNA damage-inducible protein (GADD34) signaling pathway is induced in the glaucomatous TM, and that induction of these proteins is associated with IOP elevation in dexamethasone-acetate (Dex-Ac) induced OHT mice and ROS production in glaucomatous human TM cells. ATF4 levels are found to be elevated in the TM tissues of 5-week Dex-treated mice [ 23 ], indicating that this model may appropriately recapitulate the glaucoma pathology due to ROS elevation, and SA-9 may able to scavenge them.…”
Section: Resultsmentioning
confidence: 99%
“…Both PERK and IRE1α are type I transmembrane proteins with similar ER luminal domain structures and a cytosolic Serine/threonine kinase domain, whereas ATF6α is a type II transmembrane protein that contains a cytosolic cyclic AMP response element-binding protein (CREB)–ATF basic leucine zipper domain [ 31 , 32 , 33 , 34 ]. IRE1α, PERK, ATF6 and CREBH are ultimately responsible for the activation of a set of transcription factors (TF), including spliced X-box binding protein 1 (XBP1s), activating transcription factor 4 (ATF4), CCAAT enhancer-binding protein (C/EBP) homologous protein (CHOP), nuclear factor κB (NF-κB) and activator protein 1 (AP-1), through a complicated and nonparallel process [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Er Stress and Uprmentioning
confidence: 99%